Merumuskan Islam Nusantara sebagai Sebuah Pendekatan dan Menakar Posisinya sebagai Kontra Narasi Benturan Peradaban - Bahar, Moh. Syaeful; Harnadi, Dodik (The Sociology of Islam, 2021)
The NU congress that held in Jombang on 2015 entitled with Strengthening the Islam of the Archipelago for Indonesian and World Civilization. This theme can be captured as a confidence of NU’s people and muslim society in Indonesia that have applied on Islamic model. It can positively contribute to maintain civilization and world peace. Since then, Islam Nusantara discourse keep attracting the attention of Islamic reviewers in Indonesia. This debate appear because of some researcher take the different point of view. Far apart of the debate, the Islamic style of Indonesian society has proven to be able to maintain harmonious relations between Islam and nationality. The question of how Islam Nusantara should be understood is important to discuss, so it can be applied globally. Taking advantage of several literatures that pay attention to Indonesian Islam as the main reference, this study finds two main theses. First, in order to be replicated in a different space and time, Islam Nusantara must be positioned as an Islamic approach that rests on the strength of dialogue. As an approach, Islam Nusantara has similarities with the civilization approach. However, the Islamic Nusantara approach has richer features. Second, the Islamic Nusantara approach has the potential to be a counter-narrative of the clash of civilizations thesis. If the clash of civilizations does not promise anything for the future of Islamic and western relations apart from conflict, Islam Nusantara promises a constructive dialectic for both in realizing world peace.